Effectiveness of Pneumococcal Vaccine among Chronic Respiratory Disease Monks in Priest Hospital - Jaruphat Asawaplungkul, M.D. (Journal of The Department of Medical Services, 2021)
Background : Chronic respiratory disease (CRD) has a higher incidence of community-acquired pneumonia (CAP) infected by Streptococcus pneumonia, the major cause of death. A significant reduction of CAP in the elderly has demonstrated after pneumococcal vaccination, especially when combined with influenza virus vaccination (IVV). However, the effectiveness among CRD patients remain unknown. Objective : To determine the effectiveness of 13-valent pneumococcal conjugate vaccine (PCV-13) in reduction of CAP among CRD patients. Method : A retrospective cohort study was conducted among CRD patients from 1st January 2014 to 31st May 2020 at Priest Hospital, Thailand. Patients were divided into the PCV-13 group and the non-PCV-13 group. Results : Total of 191 patients were enrolled in this study. Among these, 97 patients in the PCV-13 group (with IVV 91 patients, without IVV 6 patients), and 94 patients in the non-PCV-13 group (with IVV 55, without IVV 39 patients). Multivariable analysis showed better reduction of CAP in PCV-13 group (IRR 0.119; 95% CI = 0.018, 0.768, p = 0.025), especially when PCV-13 was given concomittantly with IVV (IRR 0.017; 95% CI = 0.001, 0.298, p = 0.005) comparing to non-vaccinated patients. However, patients in PCV-13 group were not shown the reduction rate of bronchitis (IRR 0.902; 95% CI = 0.503, 1.619, p = 0.731) and exacerbation (IRR 1.335; 95% CI = 0.683, 2.611, p = 0.398). Conclusion : 13-valent pneumococcal conjugate vaccine was demonstrated to reduce the incidence of community-acquired pneumonia in patients with chronic respiratory disease. The optimal result was found when the influenza vaccine was given concomitantly.